Holacracy as an alternative to organisations governance - Gouveia, Luis Borges (2016)
Holacracy as an alternative to organisations governance A *TRS event, Room P1.2 (Fernando Pessoa Hall), University Fernando Pessoa 16th, November, 2016, Luis Borges Gouveia This presentation introduce holacracy and discuss its use as an alternative to organize people within a corporate environment. A holacracy is a governance structure characterized by a distribution of power among self-organizing groups, rather than the top-down authority in the typical hierarchical corporate culture model. A holacracy provides a flat management structure that distributes authority. The goal of a holacracy is to ensure that those responsible for completing the work have the authority to decide how that work should be carried out. Holacracy benefits are the promises to harness agility, transparency, accountability, employee engagement and innovation. It also potentiates greater efficiency. Main critics are that the model do not allow for sufficient lateral communication. Also, it use is still emerging and we do not have sufficient evidence on holacracy advantages to rely on its promises